2007
DOI: 10.1002/cncr.22919
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic patterns at autopsy in patients with ovarian carcinoma

Abstract: Autopsy data may yield important information concerning the metastatic potential of a malignancy and may assist physicians in making clinical management decisions. The results from the current indicated that declining autopsy rates during the last decades have limited the ability of physicians to evaluate the impact of new therapy regimens on the frequency and distribution of metastases through postmortem examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 18 publications
0
58
0
2
Order By: Relevance
“…[1][2][3][4] In most autopsy reports from the last 3 decades that deal with the metastatic pattern of EOC the uterus is not listed as a metastatic site [6][7][8][9][10] probably because the patients underwent a hysterectomy before they died of the disease. In only one study of 100 autopsies of ovarian cancer 11 it is reported that the uterine serosa, the myometrium and the cervix were involved in 27%, 10%, and 3% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In most autopsy reports from the last 3 decades that deal with the metastatic pattern of EOC the uterus is not listed as a metastatic site [6][7][8][9][10] probably because the patients underwent a hysterectomy before they died of the disease. In only one study of 100 autopsies of ovarian cancer 11 it is reported that the uterine serosa, the myometrium and the cervix were involved in 27%, 10%, and 3% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ovu skupinu čine serozni i endometrioidni karcinom visokog gradusa, nediferencirani karcinom i karcinosarkom. Serozni karcinom visokog gradusa je najčešći, ne samo u ovoj skupini tumora, nego čini 70 % svih karcinoma jajnika i odgovoran je za 90 % smrti od ove bolesti 33 . Manje od 1 % seroznih karcinoma jajnika visokog gradusa u trenutku dijagnoze ograničeno je na jajnik 34 , a 5-godišnje preživ-ljenje pacijentica u IIIC stadiju bolesti, u kojem se najčešće prezentiraju, je samo 29 % 1,4 .…”
Section: Tip 2 Tumoriunclassified
“…Stoga se mogu dijagnosticirati u ranoj fazi s dosad razvijenim metodama probira koje se veći-nom temelje na transvaginalnom ultrazvučnom pregledu i mjerenjima serumske koncentracije CA 125 [8][9][10] . No, ovi tumori čine samo 25 % svih karcinoma jajnika, a odgovorni su za otprilike 10 % smrti od ove bolesti 33 . Nasuprot tome, tip 2 tumori čine 75 % svih karcinoma jajnika, a odgovorni su za 90 % letalnog ishoda bolesti.…”
unclassified
“…The liver is the fourth most common site of metastasis in recurrent ovarian cancer (OC) [1]: clinical data from living patients have shown an incidence of hepatic metastasis of approximately 9.4% [2]; moreover, several autopsy studies have indicated a major incidence of liver metastasis in relapsed OC ranging from 48% to 58.4% [1,2].…”
Section: Introductionmentioning
confidence: 99%